2011
DOI: 10.1007/s12603-011-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition risk factors among home delivered and congregate meal participants: Need for enhancement of nutrition education and counseling among home delivered meal participants

Abstract: Appropriate nutrition intervention for both HDM and CGM participants can improve health condition and delay chronic diseases. HDM participants need to be a primary focus for more effective nutrition education and counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 18 publications
2
54
0
1
Order By: Relevance
“…Three level III-2 cohort studies were identified Klein et al, 1997;Wunderlich et al, 2011). According to the NSI, up to 83% of community-dwelling older adults were at high risk of malnutrition (Ballard et al, 2013;Benedict et al, 1999;Coulston et al, 1996;Ledikwe et al, 2003;Lokken et al, 2002;Marshall et al, 1999;Marshall et al, 2001;Sharkey and Haines, 2001;Sharkey et al, 2000;Weatherspoon et al, 2004;Yap et al, 2007).…”
Section: Nutrition Screening Initiative (Nsi)mentioning
confidence: 99%
See 4 more Smart Citations
“…Three level III-2 cohort studies were identified Klein et al, 1997;Wunderlich et al, 2011). According to the NSI, up to 83% of community-dwelling older adults were at high risk of malnutrition (Ballard et al, 2013;Benedict et al, 1999;Coulston et al, 1996;Ledikwe et al, 2003;Lokken et al, 2002;Marshall et al, 1999;Marshall et al, 2001;Sharkey and Haines, 2001;Sharkey et al, 2000;Weatherspoon et al, 2004;Yap et al, 2007).…”
Section: Nutrition Screening Initiative (Nsi)mentioning
confidence: 99%
“…A nutrition assessment tool, the Patient Generated-Subjective Global Assessment (PG-SGA) was further employed to evaluate the extent of malnutrition risk in the study (Leggo et al, 2008). Other successful approaches to improve older adults' nutritional status include group nutrition education, which involved cooking demonstrations and group discussions, as well as telephone counselling (Wunderlich et al, 2011).…”
Section: Dietetic Referral and Advicementioning
confidence: 99%
See 3 more Smart Citations